2014
DOI: 10.1016/j.visres.2013.11.010
|View full text |Cite
|
Sign up to set email alerts
|

The effect of feedback on performance and brain activation during perceptual learning

Abstract: We investigated the role of informative feedback on the neural correlates of perceptual learning in a coherent-motion detection paradigm. Stimulus displays consisted of four patches of moving dots briefly (500 ms) presented simultaneously, one patch in each visual quadrant. The coherence level was varied in the target patch from near threshold to high, while the other three patches contained only noise. The participants judged whether coherent motion was present or absent in the target patch. To guarantee cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 52 publications
3
19
0
1
Order By: Relevance
“…It has been extensively investigated whether perceptual learning could modulate the mean neural activity in a cortical area. After subjects were trained with a visual detection task, the mean neural activity usually increased (Furmanski et al, 2004;Bao et al, 2010;Hua et al, 2010;Goldhacker et al, 2014), which can be explained by the increased number or improved sensitivity of relevant neural detectors. For studies in which subjects practiced a near-threshold discrimination task, the findings so far are mixed -the mean neural activity was found to increase (Schwartz et al, 2002), decrease (Schiltz et al, 1999;Mukai et al, 2007), or have little change (Op de Beeck et al, 2006;Jehee et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been extensively investigated whether perceptual learning could modulate the mean neural activity in a cortical area. After subjects were trained with a visual detection task, the mean neural activity usually increased (Furmanski et al, 2004;Bao et al, 2010;Hua et al, 2010;Goldhacker et al, 2014), which can be explained by the increased number or improved sensitivity of relevant neural detectors. For studies in which subjects practiced a near-threshold discrimination task, the findings so far are mixed -the mean neural activity was found to increase (Schwartz et al, 2002), decrease (Schiltz et al, 1999;Mukai et al, 2007), or have little change (Op de Beeck et al, 2006;Jehee et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Subjects were asked to make a two-alternative forced-choice (2-AFC) judgment of the direction of the second RDK relative to the first one (clockwise or counter-clockwise). Informative feedback was provided after each response by brightening (correct response) or dimming (wrong response) the fixation point, which could facilitate learning (Goldhacker et al, 2014). The next trial began 1 s after feedback.…”
Section: Designsmentioning
confidence: 99%
“…Interestingly, while hMT+ is strongly activated by moving stimuli, in many studies, it does not appear to show a change in response with perceptual learning, even when a motion‐related task is used [Chen et al, ]. The exception to this finding is the study of Goldhacker et al [] who found that the change in BOLD correlated with behavioural improvement in a task requiring detection of coherent motion. The contradictory results in hMT+ response may be stimulus specific, as Thompson et al [] found that some stimuli led to a reduction in hMT+ BOLD activity following training, whereas others led to an increase.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, even relatively short‐term training can cause structural changes in the brain. Demonstration of functional changes in neural activity also suggest that learning can modulate activity in visual areas, in particular V3a and hMT+ for visual motion tasks [Chen et al, ; Goldhacker et al, ; Shibata et al, ]. Interestingly, while hMT+ is strongly activated by moving stimuli, in many studies, it does not appear to show a change in response with perceptual learning, even when a motion‐related task is used [Chen et al, ].…”
Section: Introductionmentioning
confidence: 99%
“…Goldhacker et al (2014) examined the effects of informative feedback during training on perceptual learning of coherent motion and brain activity measured in fMRI in a highly systematic way. They found that informative feedback facilitates performance and, to a lesser extent, brain activity, especially for medium-to-high motion coherence levels.…”
Section: Articles In This Special Issuementioning
confidence: 99%